Strategi Kepemimpinan Kepala Madrasah terhadap Efektivitas Kerja Sama Tim di MIN 20 Aceh Besar - Mardin Mardin; Hikmah Mardyanto (LaKaspia, 2025)
This study aims to examine the strategies and challenges of school principals in managing teamwork at MIN 20 Aceh Besar, and to compare them with the findings of previous studies by Dewi (2021) and Munandar (2022). This study uses a qualitative approach with data collection techniques through observation, interviews, documentation, and triangulation involving various school stakeholders. The results show that the principal's leadership strategies are implemented collaboratively, participatively, and contextually based on the school's work culture. These strategies include joint planning, team involvement in task distribution, delegation based on competence, and clarity of authority. In addition, regular monitoring and evaluation are carried out, as well as capacity building through structured training programmes. The main challenges faced are differences in the level of commitment among team members and limited technical skills. Nevertheless, trust among team members has been well established. Communication barriers are overcome through coordination forums and regular discussions. The headmaster continues to strive to improve team performance through planned training and development to overcome various limitations and strengthen collaborative commitment